Case 8: A 58-Year-Old Man Presented With Symptomatic Recurrent Pulmonary Edema - Lee, Su Nam; Kim, Gee-Hee; Choi, Joonsung; Kim, Min-Sik (Journal of Korean medical science, 2023)
KCI Citation Count: 0